Private equity - nowe możliwości dla polskich przedsiębiorstw - Fałat-Kilijańska, Ilona (Private Equity - New Opportunies for Polish Enterprises, 2005)
This publication contains main definitions of private equity. It explains how the private equity works, what kind of enterprises it chooses, how it supports entrepreneurs and shows routes of exiting. It also demonstrates the positive advantages that private equity brings to the business and the economy. Readers can find some interesting findings of the European Private Equity & Venture Capital Association. The second part of the article shows beginnings of the Polish private equity market and a dramatic increase in private equity investment in Polish companies. It indicates chances and barriers for developing of our private equity investments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 115-127